PSXI-8 Corn stover feedlot diets with elevated mycotoxins and binder effect on cattle performance. (30th November 2020) - Karls, Caleb; Schaefer, Mitch; Schaefer, Dan
Abstract: Weather conditions often dictate the quality of corn, corn silage, and corn stover harvested for livestock feed. When growing and/or harvest conditions are wet, mycotoxin producing fungi can flourish. Mycotoxin levels were determined to be elevated in the fall 2018 corn crop (Table 1). A 3 x 2 factorial experiment was initiated to observe effects of a mycotoxin binder, hydrated sodium calcium aluminosilicate (Engage-M, United Animal Health, Sheridan, IN), on cattle performance. Three treatment diets with elevated mycotoxin levels were amended with Engage-M fed at 0 or 14 g hd -1 d -1 . Steers (n = 72, 12 pens total) were fed during Grow (21 d) and Finish (51 d) phases. During the Grow phase a 52% corn silage, 20% DDGS, and 8% supplement basal diet was fed and treatments were an additional 20% diet DM included as corn silage (CSIL), conventional corn stover (CST), or single-pass bale stover (SPB). Cattle fed Engage-M during Grow phase had numerically higher daily gains, 1.35 kg d -1, compared to no binder, 1.26 kg d -1 (P = 0.17). During the Finish phase, all cattle were fed similarly (72.1% rolled corn, 12% corn silage, 8.9% DDGS, 7% supplement diet DM). Cattle fed Engage-M tended (P = 0.09) to have increased daily gains, 2.07 kg d -1, compared to no binder, 1.9 kg d -1 . Dry matter intake was similar for both treatments during the Finish trial, 12.9 kg hd -1 d -1 (P = 0.83), suggesting the increase in cattle performance was due to improved utilization of feed and not feed intake. The Finish phase feed to gain ratio was 6.25 vs. 6.83 (P = 0.06) with and without Engage-M, respectively. The trend was for cattle fed Engage-M to be 9.2% more efficient. The present study suggests that feeding Engage-M may increase cattle performance when diets have elevated levels of zearalenone and vomitoxin.